The relationship between real earnings management and operational financial security in industrial listed companies - Comporek, Michał (Relacje między realnym zarządzaniem zyskiem a operacyjnym bezpieczeństwem finansowym przemysłowych spółek giełdowych, 2020)
A company’s financial result is a multidimensional and diverse category of primary importance for the continuation and development of the business entity’s activity. The varied expectations of individual groups of enterprise stakeholders regarding the quality of information contained in the reported data imply that managers often face various types of market and contractual ‘challenges’ affecting the directions and scale of the intentional shaping of the company’s financial results. The main purpose of the paper is to present the relationships between real earnings management practices and the operational financial security of industrial listed companies. The research was carried out on a sample of 72 public enterprises classified into twelve industries whose shares were traded on the Warsaw Stock Exchange for at least twelve years in the period 2003-2018
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 31-41
Keywords: real earnings management; operational financial security; industrial enterprises; Warsaw Stock Exchange; realne zarządzanie zyskiem; opeacyjne bezpieczeństwo finansowe; spółki giełdowe; Giełda Papierów Wartościowych w Warszawie